Financial Risk Management in 2020's Recession: Evidence from ASEAN Countries - Andreas Krisvian; Rofikoh Rokhim (Petra International Journal of Business Studies, 2022)
This study aims to determine the effect of bank financial risk consisting of liquidity risk, credit risk, and other factors on bank stability. This study took samples from 41 open conventional banks in five ASEAN countries that experienced crises, namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. The analysis methods used in this study are a combination of simultaneous and non-simultaneous GMM and VECM for the data period between Q-4 2015 to Q-3 2020. It covers the period before and during the crisis. This study found a reciprocal effect of the two financial risks on bank stability in the long term, an effect of the combined two risks on bank stability in the short term, and other factors that also affect each of the risks and bank stability. The results of this study can provide further knowledge about bank financial risk management that can be useful for reducing the potential for bank bankruptcy during a crisis.